Paving the Way for Pandemics: Proximate and Remote Causes of COVID-19 - Waizbort, Ricardo (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2024)
This paper investigates how the historians Donald Worster and Dipesh Chakrabarty, independently, employ the concept of remote causes in their assessment of causes of the COVID-19 pandemic. After introducing these two categories within the sphere of the evolutionary theory, we will try to show that both historians argue that evolutionary theory is necessary, but certainly not sufficient, to understand how humans interact with other species, especially animals (wild and domesticated), which is related to the spillover of pathogenic species. They note that the human impulse to control and manipulate natural phenomena for our own benefit is an evolutionary adaptation that has gotten out of control and was one of the fundamental remote causes of the pandemic. We conclude with a call for closer ties between medicine informed by evolutionary theory and the social sciences in an attempt to combine proximate and remote causes and better understand humankind’s place in nature, along with the politic e societal risks of utilizing natural resources without taking this into account.